Death Anxiety, Reliability, Validity, and Factorial Structure of the Farsi Form of the Arabic Scale of Death Anxiety in Iranian Old-Aged Persons. (27th October 2016) - Dadfar, Mahboubeh; Lester, David; Bahrami, Fazel
Abstract : The present study is aimed at examining the level of death anxiety and the sex-related differences among old-aged Iranian individuals sample to compare the old-aged persons with young college students and to explore the psychometric properties of the Arabic Scale of Death Anxiety (ASDA) factors in old-aged sample. A sample of 146 volunteer Iranian individuals took part in the study. The mean ages were 68.58 (SD = 7.10), men 68.81 (SD = 7.44) and women 68.28 (SD = 6.76), respectively. The mean score of the ASDA was 51.09 (SD = 20.19). Cronbach's alpha of the ASDA was found to be high (0.94); and Spearman-Brown coefficient was 0.92. Women had a significantly higher mean total score on the ASDA. Old-aged individuals had a significantly higher mean ASDA total score than younger college students (M age = 25.77). The factor analysis of the ASDA items yielded three factors accounting for 67.88% of the total variance labeled (F1) fear of dead people and tombs; (F2) fear of lethal disease and postmortem events; and (F3) death fear. These factors were highly replicable with previous factors extracted from a middle-aged Kuwaiti sample. On the basis of the present results, there are the following three general conclusions: death anxiety is not significantly correlated with age; the sex-related differences on death anxiety are striking in the Iranian samples; and the ASDA has a highly replicable factor structure among two Iranian and Arab countries.